Figurines. A Microcosmos of Clay. An Exhibition - Angeliki Koukouvou (Les Carnets de l’ACoSt)
A major exhibition opened at the Archaeological Museum of Thessaloniki on April 3, 2017. Entitled “Figurines. A Microcosmos of Clay,” this exhibition presents some 617 terracotta figurines from Macedonia and Thrace that range in date from the early Neolithic period to late antiquity.